Safety barrier performance assessment based on multi-phase Markov model and EPN: Application to FPSO gas leakage - Yu, Jianxing; Zeng, Qingze; Yu, Yang; Zhang, Baolei; Ding, Hongyu; Ma, Wentao; Wu, Shibo; Li, Zhenmian (Ocean engineering, 2025)
The FPSO topside module has a risk of gas leakage during oil and gas treatment, and safety barriers are required to prevent accidents from escalating and avoid catastrophic consequences. To ensure the high reliability of safety barriers in responding to accidents, it is necessary to conduct performance assessment to quantify the performance of safety barriers during operation. This study proposes a safety barrier performance assessment framework based on multi-phase Markov model and event Petri net (EPN) for dynamic performance analysis of safety barriers and assessment of the probability of gas leakage accident escalation. First, identify the safety barriers involved in FPSO gas leakage, and establish the alarm interlocking logic of the safety barriers. Then, the multi-phase Markov model is used to evaluate the availability of safety barriers, which can deal with the dynamic effects of continuous testing and maintenance on barrier performance. Finally, the EPN model of FPSO gas leakage accident evolution is established based on the interlocking logic of safety barriers, and the probability of accident escalation is quantitatively evaluated by combining the availability and effectiveness of safety barriers. The implementation process of the proposed method is illustrated by a case study, and the impact of different test strategies and characteristic parameters on the safety barrier performance is explored through relevant analysis. The assessment results can provide useful references for improving the performance of safety barriers, and have important practical significance for reducing the accident escalation probability and ensuring the safety production of FPSO. •A quantitative performance assessment framework of safety barriers for FPSO gas leakage is proposed.•The improved multi-phase Markov models integrating multiple characteristic parameters are established to quantify the availability of safety barriers.•An event Petri net (EPN) method is proposed to evaluate various consequences of accident escalation.•The EPN model of FPSO gas leakage accident escalation is presented.•The method is illustrated in a case study on the safety barriers of FPSO gas leakage.